Relationship between the progression of posterosuperior rotator cuff tear size and shoulder abduction function: A cadaveric study via dynamic shoulder simulator - Wang, Liren; Kang, Yuhao; Jin, Haocheng; Wang, Mingqi; Wei, Yiyao; Gao, Haihan; Shi, Dingyi; Yu, Suiran; Xie, Guoming; Jiang, Jia; Zhao, Jinzhong (Frontiers in Bioengineering and Biotechnology, 2022)
Posterosuperior rotator cuff tear (PSRCT) is one of most common shoulder disorders in elder people’s daily life, however, the biomechanical relationship between PSRCT and shoulder abduction function is still controversial. Herein, a bionic dynamic shoulder abduction stimulator was invented to reveal the sealed biomechanism. Totally, twelve freshly frozen cadaveric shoulders were included and tested in five conditions: intact rotator cuff, 1/3 PSRCT, 2/3 PSRCT, entire PSRCT, and global RCT. In each condition extra load (0%, 45%, and 90% failure load) was sequentially added on the distal humerus, and the function of the remaining rotator cuff was mainly evaluated via the middle deltoid force (MDF) required for abduction. It is found that the peak MDF required for abduction did not differ among the three PSRCT conditions (1/3 PSRCT: 29.30 ± 5.03 N, P = 0.96; 2/3 PSRCT: 29.13 ± 9.09 N, P = 0.98; entire PSRCT: 28.85 ± 7.12 N, P = 0.90) and the intact condition (29.18 ± 4.99 N). However, the peak MDF significantly differed between the global RCT (76.27 ± 4.94 N, P < 0.01) and all PSRCT and intact conditions. Under 45% failure load, the MDF of entire PSRCT and global tear conditions were significantly increased compared with other status. With the 90% failure load, only the 1/3 PSRCT condition maintained the same shoulder function as the intact rotator cuff. These biomechanical testing jointly suggested that the weight-bearing ability of the shoulder significantly decreased as PSRCT progressed.